Research Progress on MRI for White Matter Hyperintensity of Presumed Vascular Origin and Cognitive Impairment - Meng, Fanhua; Yang, Ying; Jin, Guangwei (Frontiers in Neurology, 2022)
White matter hyperintensities of presumed vascular origin (WMH) is a common medical imaging manifestation within the brain of middle-aged and elderly people. WMH can lead to cognitive decline and increase the risk of cognitive impairment and dementia. However, the pathogenesis of cognitive impairment in patients with WMH remains unclear. Magnetic resonance imaging (MRI) is an indispensable tool for the detection of WMH, and novel MRI techniques play an increasingly important role in the exploration and research of WMH and cognitive impairment. WMH increases the risk of cognitive impairment, and the nature and severity of its related cognitive impairment depend on the volume, location of the lesion and the patient's cognitive reserve. There are abnormal changes in microstructure, cerebral blood flow, metabolites, and resting brain function in WMH patients with cognitive impairment. In this article, we provide an overview of the association between WMH and cognitive impairment and the application of diffusion tensor imaging, 3D-arterial spin labeling, magnetic resonance spectroscopy, and resting state functional magnetic resonance imaging in WMH and cognitive impairment.